2014
DOI: 10.2485/jhtb.23.225
|View full text |Cite
|
Sign up to set email alerts
|

Medial Pterygoid initiated the Growth of the Mandible through Premature Muscle Contraction

Abstract: Craniofacial growth is influenced by the interaction of muscle and bone tissues. The medial pterygoid (MP) is one of the muscles of mastication attached to the mandible. The purpose of the study was to investigate the relation between the MP and mandible during embryogenesis. Specimens were prepared from fifty fetal mice at embryonic day (ED) 12.5, 13.5, 14.5 and 15.5. Slides were stained with hematoxylin and eosin (H&E) and observed under the light microscope. Immunohistochemistry using desmin, a muscle speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Moreover, our previous studies have suggested that muscle anlagen are already fitted onto the surface of the adjacent bone or cartilage analgen during the prenatal development [21][22][23][24][25][26][27]. Therefore, the interaction between the muscle and bone may affect their shape during the developmental period because the skeletal muscles properly fit onto the surfaces of adjacent bone for a lifetime, including in the fetal period [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous studies have suggested that muscle anlagen are already fitted onto the surface of the adjacent bone or cartilage analgen during the prenatal development [21][22][23][24][25][26][27]. Therefore, the interaction between the muscle and bone may affect their shape during the developmental period because the skeletal muscles properly fit onto the surfaces of adjacent bone for a lifetime, including in the fetal period [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%